Anisotropy of critical indices of ferroelectric phase transition in TGS crystals by the optical interference investigation - Andriyevsky, B.V.; Myshchyshyn, O.Ya.; Romanyuk, M.O. (Condensed Matter Physics, 1999)
Temperature dependences of the optical path difference, variable part of the refractive index and thickness of triglycine sulphate crystal for three crystallophysic directions are studied in the temperature range of 39–70 °C, including the ferroelectric phase transition at Tc=49 °C, using the Jamen type optical interferometer. Temperature dependences of the spontaneous changes of the characteristics studied in the range of 39–49 °C are ﬁtted by the power-like low Y ∼ τ²β with doubled averaged effective critical indices 2β=0.87–0.95. The 2β values being different from the unity is explained by the essential temperature dependence of the coefﬁcients of electrooptic, inverse piezoelectric and electrostriction effects in the range close to the phase transition point. Досліджено температурні залежності оптичної різниці ходу, змінної частини показника заломлення і товщини кристала тригліцинсульфату для трьох кристалофізичних напрямів в області температур 39– 70 °C, що містить температуру Tc=49 °C сегнетоелектричного фазового переходу, використовуючи оптичний інтерферометр типу Жамена. Температурні залежності спонтанних змін досліджуваних характеристик в області 39–49 °C апроксимовані степеневими залежностями Y ∼ τ²β з подвоєними засередненими ефективними критичними індексами 2β = 0.87 − 0.95. Відмінність 2β від одиниці пояснюється суттєвою температурною залежністю поблизу точки фазового переходу коефіцієнтів електрооптичного, оберненого п’єзоелектричного ефектів та електрострикції.